A pH-sensitive guar gum-grafted-lysine-β-cyclodextrin drug carrier for the controlled release of 5-flourouracil into cancer cells. Issue 10 (22nd February 2018) - Praphakar, Rajendran Amarnath; Jeyaraj, Murugan; Mehnath, Sivaraj; Higuchi, Akon; Ponnamma, Deepalekshmi; Sadasivuni, Kishor Kumar; Rajan, Mariappan
Abstract : The physiological environment is a crucial factor in biomedical systems, which can be regulated with relative ease both in vitro and in vivo . Abstract : The physiological environment is a crucial factor in biomedical systems, which can be regulated with relative ease both in vitro and in vivo . Control of pH has emerged as a powerful strategy in cancer therapy because pH has a profound effect on the interaction of a polymeric-based drug delivery system with tumor cells. In this regard, the enhancement of pH response capability was demonstrated with a 5-flourouracil (5-FU)-loaded guar gum (GG)- grafted -lysine-β-cyclodextrin (L-β-CD) drug carrier. The size, charge, morphology, and encapsulation efficiency of the 5-FU-loaded polymeric carrier were characterized for the control and sustained release of the drug. In a specific cancer pH environment, 5-FU-loaded GG- g -L-β-CD could rapidly swallow, disassemble, and release 5-FU by accepting or losing electrons. In vitro observations indicate that GG- g -L-β-CD dramatically releases 5-FU in an acidic environment rather than in a basic environment. In vitro antitumor activity tests showed that 5-FU-loaded GG- g -L-β-CD had a higher cytotoxicity against KB cells, with an IC50 value of 1.38 μg ml −1 . The reactive oxygen species (ROS) generated by 5-FU in the KB cells showed efficient suppression of tumour cell growth. The Hoechst assay revealed the active nature of 5-FU in the cell nucleus of the KB cells. The potential mitochondrial damage by apoptosis in KB cells greatly increased cell death. Therefore, due to its active nature, the pH-sensitive 5-FU-loaded GG- g -L-β-CD carrier is a potential drug delivery system for safe and effective cancer therapy, and it can be useful for inhibiting tumour cell growth.